Effect of Marketing Strategy and Service Quality Against the Decisions of Parents - Safitri Amelia; Hartini Salamah; Mohammad Sofyan (Yayasan Ilomata, 2019)
This study aims to analyze and determine the effect of marketing strategy variables and service quality on parents' decisions. In this study, the dimensions of marketing strategies include products, prices, promotions, places, people, processes and physical evidence. Service quality dimensions include reliability, responsiveness, confidence, empathy and tangibility. Quantitative methods with multiple linear regression analysis were processed using SPSS for windows version 22. The results showed that there were simultaneously the effects of marketing strategy and service quality variables on parents' decisions. Partially, the marketing strategy variable did not significantly influence the parents' decisions at PAUD Al Hidayah Pertiwi. While service quality variables significantly influence the decisions of parents of students in PAUD Al Hidayah Pertiwi.